Estimating regimen‐specific costs of chemotherapy for breast cancer: Observational cohort study. Issue 22 (10th October 2016) - Giordano, Sharon H.; Niu, Jiangong; Chavez‐MacGregor, Mariana; Zhao, Hui; Zorzi, Daria; Shih, Ya‐Chen Tina; Smith, Benjamin D.; Shen, Chan
Abstract : BACKGROUND: One goal for high‐quality patient care is communicating treatment costs to patients, yet cost information can be elusive. This is especially relevant for breast cancer care, for which numerous guideline‐concordant adjuvant chemotherapy regimens exist. The objective of the current study was to generate cost estimates for such regimens from payers' and patients' perspectives in a large, insured US population. METHODS: Adult women who had incident breast cancer diagnosed between 2008 and 2012 (from the MarketScan database), had no secondary malignancy within 1 year of diagnosis, and received chemotherapy within 3 months of diagnosis were included (n = 14, 643). Total and out‐of‐pocket costs were calculated using all claims within 18 months of diagnosis and were normalized to 2013 US dollars. The extended estimating equations method was used to assess cost by regimen adjusting for demographic and clinical factors. RESULTS: Among patients who did and did not receive trastuzumab, the median insurance payments were $160, 590 and $82, 260, respectively, and the median out‐of‐pocket payments were $3381 and $2724, respectively. Among patients who did not receive trastuzumab, 25% paid more than $4712, and 10% of patients paid more than $7041. For patients who did receive trastuzumab, 25% paid more than $5604, and 10% paid more than $8384. Among patients who were covered by high‐deductible health plans, the median out‐of‐pocket cost was $5158, 25% paid at least $8128, and 10% paid ≥ $11, 344. CONCLUSIONS: The costs of breast cancer chemotherapy vary widely across regimens, and patients bear a substantial out‐of‐pocket burden. Cancer 2016;122:3447–3455 . © 2016 American Cancer Society Abstract : The costs of breast cancer chemotherapy vary widely across regimens and patients bear a substantial out‐of‐pocket burden. These cost‐of‐care data can help inform discussions between patients and providers to ensure the selection of financially appropriate breast cancer therapies.